Strengthening the research of key enabling technologies for new innovations - Sanja Tišma; Karolina Horvatinčić; Iva Tolić; Anamarija Farkaš (Economic Review: Journal of Economics and Business, 2019)
The development of science and technology in recent times is hosting major changes with the emergence of new key concepts, e.g. nanote- chnology, micro nanoelectronic, etc. Techno- logies are changing the way in which society operates and there is a need to ensure that they are used in a best possible way. The way to address these new concepts is crucial for achi- eving economic and social prosperity and an obvious indicator of a country's ability to main- tain a sustained growth in accordance with the latest advances. In Croatia, key enabling tech- nologies (KETs) are recognized as one of the two cross-cutting topics able to create the biggest addedvalue and foster the emergence of new economic activities, the rising of the pro- ductivity of the Croatian economy and the creation of new and sustainable job opportu- nities in the Croatian Smart Specialization Strategy. In addition, Croatian scientific and research institutions have a lot of experience in KET-related projects funded by the European Union, either as a partner in international projects or having their own project. The biggest Croatian stren-gth in KET are open economy and relatively high-level of internatio- nalisation of national companies, as well as the access to a pool of high-skilled workers and good quality infra-structures with substantial investments in the fields of transportation, telecommunications and energy. However, the- re is limited colla-boration between industry and academia in R&D and there is a need to further support and train SMEs.
Keywords: O31; O32; O33; O19; 330; innovation; research and development; KETs; international cooperation; eco-nomic development